2014
DOI: 10.1175/jcli-d-14-00121.1
|View full text |Cite
|
Sign up to set email alerts
|

A Weibull Approach for Improving Climate Model Projections of Tropical Cyclone Wind-Speed Distributions

Abstract: Reliable estimates of future changes in extreme weather phenomena, such as tropical cyclone maximum wind speeds, are critical for climate change impact assessments and the development of appropriate adaptation strategies. However, global and regional climate model outputs are often too coarse for direct use in these applications, with variables such as wind speed having truncated probability distributions compared to those of observations. This poses two problems: How can model-simulated variables best be adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 48 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Given the observations of extreme windstorms, it has been demonstrated that it is necessary to fit a left‐truncated Weibull (LTW) distribution to the set of maximum wind speeds . For a nonnegative truncation parameter, u , the left‐truncated Weibull CDF for wind speeds w is given by Ffalse(wfalse|a,b,ufalse)=1exp[]()uab()wab1emfor1emw>u. …”
Section: Methodsmentioning
confidence: 99%
“…Given the observations of extreme windstorms, it has been demonstrated that it is necessary to fit a left‐truncated Weibull (LTW) distribution to the set of maximum wind speeds . For a nonnegative truncation parameter, u , the left‐truncated Weibull CDF for wind speeds w is given by Ffalse(wfalse|a,b,ufalse)=1exp[]()uab()wab1emfor1emw>u. …”
Section: Methodsmentioning
confidence: 99%
“…It is also too coarse to capture the intensity of the strongest hurricanes (as discussed in Done et al, 2015). Rather than downscaling the NARR data to obtain these small-scale details using dynamical (e.g., Laprise et al, 2008) or statistical (e.g., Tye et al, 2014) methods (which could introduce further uncertainties), we choose to sacrifice the small-scale details of the wind field and peak hurricane intensity for location accuracy of the NARR data. To account for these missing wind extremes, all wind speed values are normalized by the maximum value of wind speed in the data set.…”
Section: Statistical Methodology and Data Descriptionmentioning
confidence: 99%
“…As the hurricane intensity is not known in advance, β is treated as a random variable with distribution Ψ( β ). Tye, Stephenson, Holland, and Katz () note that the Weibull distribution has long been established as a useful probability distribution function for modeling hurricane wind speed. Grigoriu () reports that an extensive record of hurricane wind speeds is available at the NIST (National Institute of Science and Technology), which the author and others have used to establish the distribution parameters of Ψ( β ).…”
Section: The Frameworkmentioning
confidence: 99%